Antioxidants to Supplement or Not to Supplement That Is the Question - Stanley Omaye; Nabil Elsayed (MDPI AG, 2012)
Antioxidants, whether from diet or pharmacological supplementation, gained significant popularity among scientists and lay public in recent years, and was claimed to protect or treat numerous ailments. [...]